Extent of spike shedding and stem wilting of pepper (Piper nigrum L.) in Morogoro District, Tanzania - Abdul Jafari Shango; Ramadhani Omari Majubwa; Amon Petro Maerere (CABI Agriculture and Bioscience)
Abstract Background Pepper (Piper nigrum L.) is an important spice produced by small-scale farmers in Morogoro district of Tanzania for both local and export markets. Recently, farmers have reported a decline in crop productivity due to spike shedding and stem wilting of pepper plants. The study was conducted to obtain baseline information on the extent of the disorders. Methods An altitudinal transect survey was conducted in Morogoro district from October to November 2018. Data were collected from 216 pepper farmers through a questionnaire, focus group discussions, and field observations. Chi square tests (α = 0.05) were used to compare differences between gender, pepper cultivars by wards and yield, spike shedding and stem wilting by pepper cultivars and plant species used to support pepper vines. Fisher’s exact test at (α = 0.05) was used to compare the effects of production constraints and altitude. A regression analysis was performed to explore the relationship between altitude and the incidence of spike shedding and stem wilting. Results The majority of interviewees (69%) had observed spike shedding and stem wilting of pepper on their farms for > 3 years. Spike shedding was more prominent at 300 meters above sea level (masl, 85.7%), while stem wilting was reported by most (66.7%) farmers at 457 masl. The most affected pepper cultivar was reported to be “Babu kati” in Mtombozi (19.2% of respondents) and “Ismailia” in Mkuyuni and Kibogwa (28.9% of respondents) wards, while in Kibungo ward cultivar “Babu ndogo” (85.7% of respondents) and in Konde ward cultivar “Babu kubwa” (53.8% of respondents) were most affected. Approximately 53% of respondents reporting the disorders used Jatropha to support the pepper vines, and 93% of the farmers reported the disorders to occur during the dry season. A greater proportion of the interviewed farmers (92.1%) reported applying no measures to control spike shedding and stem wilting of pepper. Conclusions Incidence of spike shedding and stem wilting was higher at a low altitude compared to high altitude areas. The magnitude of the disorders differed among pepper cultivars regardless of support plants species used. Poor adoption of key agronomic practices and lack of any information on control measures may be contributing to the high incidence of the disorders in the study area. The study demonstrates the extent of the problem, and provides a baseline for identifying the causal agent(s) of spike shedding and stem wilting, which in turn will allow appropriate control measures to be selected.